2022
DOI: 10.3390/nano12101668
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Phase Transformations in Nanocrystalline Ag2S Silver Sulfide in a Wide Temperature Interval and Influence of Nanostructured Ag2S on the Interface Formation in Ag2S/ZnS Heteronanostructure

Abstract: Phase transformations that take place in nanocrystalline Ag2S silver sulfide have been systematically studied at temperatures from 298 to 893 K. The crystal structures of the polymorphic modifications α-Ag2S, β-Ag2S, and γ-Ag2S of nanocrystalline Ag2S have been found. It is established that the interstitial spacings between ions of silver in the superionic phases β-Ag2S and γ-Ag2S are noticeably smaller than diameter of the Ag+ ion. As a result of which, the probabilities of filling the sites of the metal subl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 81 publications
0
0
0
Order By: Relevance
“…Authors observed that by increasing the temperature to around 450 K, nanoparticles grow insignificantly, which indicates the thermal stability of silver sulfide up to this temperature [60]. The authors of the work reported the phase transformation of silver sulfide synthesized via hydrochemical deposition method over a wide range of temperatures [7]. Raid A Ismail et al investigated the effect of deposition time on the synthesis of Ag 2 S nanofilm.…”
Section: Hydrochemical Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors observed that by increasing the temperature to around 450 K, nanoparticles grow insignificantly, which indicates the thermal stability of silver sulfide up to this temperature [60]. The authors of the work reported the phase transformation of silver sulfide synthesized via hydrochemical deposition method over a wide range of temperatures [7]. Raid A Ismail et al investigated the effect of deposition time on the synthesis of Ag 2 S nanofilm.…”
Section: Hydrochemical Depositionmentioning
confidence: 99%
“…Among various metal sulfides, silver sulfide (Ag 2 S) is a distinctive binary metal chalcogenide semiconductor material with a narrow and direct band gap of around 1ev and high absorption coefficient of approximately 10 6 cm [4][5][6]. Studies suggest that silver sulfide has a layered structure that exists in three polymeric forms [7]. Phase diagrams [8] predict that below 450 K α-Ag 2 S, the semiconducting phase exists.…”
Section: Introductionmentioning
confidence: 99%
“…増え不規則構造化すること [23][24][25] ,後二者の高温相は S 2 − 格 子内に多数箇所存在するカチオンサイトにカチオンが分 散分布するため液体状態に近いこと [26][27][28][29] が知られており,…”
Section: 緒言unclassified